Staying On: Reminiscences of Early Post-Occupation Japan - Rabinowitz, Richard W. (Zeitschrift für Japanisches Recht, 2004)
I. Arrival II. Deeper Motivational Impulses and Quasi-Random Chance III. Settling In IV. Bar Association Membership V. The Significance to Us of the Legal Studies Program VI. Our Temporary Stay Abroad VII. Resumption of Our Residence in Japan VIII. My Exposure to Law Practice IX. The Dual Regimen X. Concurrent Activity: 1956 – 1960 XI. Our Decision to Stay On XII. The Final Precipitants of the Decision to Stay On